PENGARUH PEMBERIAN MYOINOSITOL DAN ARANG AKTIF PADA MEDIA SUB KULTUR JARINGAN TANAMAN ANGGREK (Dendrobium SP) - PEBRA HERIANSYAH; TRINOP SAGIARTI; ROVER ROVER (Jurnal Agroteknologi, 2014)
The study was carried out at the Laboratory of Plant Biotechnology Faculty of Agriculture, University of islam Riau Pekanbaru. The timing of the study during the three months from October to December 2013. The design used in this study is the factorial experiment in completely randomized design (CRD), which consists of two factors and three replications. The first factor is the provision of Myoinositol: A0 (0 mg/l), A1 (25 m/l), A2 (50 mg/l), and A3 (75 mg/l).While the second factoris the provision of active charcoal: B0 (0 g/l), B1 (1 g/l), B2 (2 g/l), and B3 (3 g/l). From the results of this study concluded that the provision of various concentration of Myoinositol treatment singely provide significant effect on all parameters of the observations with the best treatment A2 (50 mg/l Myoinositol administration) that age emerged shoots (20,25days), sum up shoot (2,11 fruit) shoot height (2,32 cm), sum up roots (3,00 fruit) and weight wet roots (26,39 mg). Treatment provision of various consentrations of active charcoal.Singely provide significant effect on all parameters of the observations with the best treatment B2 (1 g/l active charcoal administration) that age emerged shoots (23,92 days), sum up shoot (2,06 fruit)shoot height (2,01 cm), sum up roots (2,67 fruit)and weight wet roots (25,59 mg). Interactions are granting various concentrations of Myoinositol and active charcoal provide significant effect of the parameters of the observation age emerged shoots with the best treatment in the combination treatment A2B0 (16,33 days), and weight wet roots with the best treatment A2B0 (47,47 mg) Myoinositol, Arang Aktif, Anggrek.